Resistive Ferroresonance Limiter for Potential Transformers. (11th November 2012) - Radmanesh, Hamid; Gharehpetian, G. B.; Fathi, Hamid
Abstract : The ferroresonance or nonlinear resonance is a complex phenomenon, which may cause overvoltage in the electrical power system and endangers the system reliability and operation. The ability to predict the ferroresonance in the transformer depends on the accuracy of the transformer model used. In this paper, the effect of the new suggested ferroresonance limiter on the control of the chaotic ferroresonance and duration of chaotic transients in a potential transformer including nonlinear core losses is studied. To study the proposed ferroresonance limiter, a single phase 100 VA, 275 kV potential transformer is simulated. The magnetization characteristic of the potential transformer is modeled by a single-value two-term polynomial. The core losses are modeled by third order power series in terms of voltage and include core nonlinearities. The simulation results show that the ferroresonance limiter has a considerable effect on the ferroresonance overvoltage.